Du modèle « enabling » au contrôle capacitant : état de l’art et perspectives - Benoit, Benjamin; Chatelain-Ponroy, Stéphanie (Finance Contrôle Stratégie, 2016)
Enabling control appeared twelve years ago from research developed by Ahrens and Chapman (2004). It can be read as an innovative approach to a blind spot in the literature. Calling to arms a growing number of researchers, it seduces by the promise of overcoming traditional models but it suffers from a lack of precision of its concepts resulting in operational difficulties. This paper analyzes the conceptual basis of enabling control by placing it in relation to empirical studies. It offers avenues of research to enable a better understanding of it.
Keywords: enabling continuum; enabling control; enabling dual role; management control system; user-manager.